Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières - Larocque, Sylvie; Lavoie, Anne. Marise; Muray, Kalum; Waja, Chamberline (Revue de la Diversité de la Recherche en Santé, 2021)
fs-ref-orig: Larocque, S., Lavoie, A. M., Muray, K. et Waja, C. (2021). Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières. Revue de la Diversité de la Recherche en Santé, 4, 33-48. https://pubs.biblio.laurentian.ca/index.php/drhj-rdrs/Article de revue /view/324/287 fs-code-orig: Larocque-2021

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport

Pratique # 20 : Talking About Mental Illness (TAMI) en français (Territoires du Nord-Ouest) - Michel, Jean Nephetaly; van Kemenade, Solange; Benoît, Josée (2021)
fs-ref-orig: Michel, J.N., van Kemenade, S. & Benoît, J. (2021, mise à jour 2025). Pratique # 20 : Talking About Mental Illness (TAMI) en français (Territoires du Nord-Ouest). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Michel-2025

Sense of belonging and social climate in an official language minority post-secondary setting - Penner, Kailey; de Moissac, Danielle; Rocque, Rhéa; Giasson, Florette; Prada, Kevin; Brochu, Paul (Canadian Journal of Higher Education, 2021)
Perceived sense of belonging and positive social climate on campus are crucial elements for post-secondary students, as they contribute to academic achievement, positive mental health, and help-seeking. Few studies have explored post-secondary students’ sense of belonging and perceptions of social climate in an official language minority campus, which attract Canadian-born francophones, anglophones who pursue higher education in their second language, and francophone international students. With declining student mental health and greater ethnolinguistic diversity of post-secondary students on Canadian campuses, this important study aims to explore francophone students’ perceived sense of belonging and social climate on campus. In total, 35 students from different ethnolinguistic backgrounds took part in focus groups or individual interviews. Domestic students with French as their first language more often reported positive social climate on campus and a sense of belonging, in contrast to international students and students with French as a second language. A common obstacle to connecting with others was language insecurity in one of the official languages, as both are currently used on campus. Universities hosting students of multiple linguistic diversities should provide courses and campus events to stimulate intercultural knowledge and dialogue.